Interferon-Stimulated Genes are Transcriptionally Repressed by PR in Breast Cancer - Walter, Katherine R. (Mol Cancer Res, 2017)
The progesterone receptor (PR) regulates transcriptional programs that drive proliferation, survival, and stem cell phenotypes. Although the role of native progesterone in the development of breast cancer remains controversial, PR clearly alters the transcriptome in breast tumors. This study identifies a class of genes, interferon-stimulated genes (ISGs), potently downregulated by ligand-activated PR which have not been previously shown to be regulated by PR. Progestin-dependent transcriptional repression of ISGs was observed in breast cancer cell line models and human breast tumors. Ligand-independent regulation of ISGs was also observed, as basal transcript levels were markedly higher in cells with PR knockdown. PR repressed ISG transcription in response to interferon treatment, the canonical mechanism through which these genes are activated. Liganded PR is robustly recruited to enhancer regions of ISGs, and ISG transcriptional repression is dependent upon PR’s ability to bind DNA. In response to PR activation, key regulatory transcription factors that are required for interferon-activated ISG transcription, STAT2 and IRF9, exhibit impaired recruitment to ISG promoter regions, correlating with PR/ligand-dependent ISG transcriptional repression. Interferon activation is a critical early step in nascent tumor recognition and destruction through immune surveillance. As the large majority of breast tumors are PR-positive at the time of diagnosis, PR-dependent downregulation of interferon signaling may be a mechanism through which early PR-positive breast tumors evade the immune system and develop into clinically relevant tumors. Implications: This study highlights a novel transcriptional mechanism through which PR drives breast cancer development and potentially evades the immune system.